Hubungan Pola Asuh Orang Tua Terhadap Kedisiplinan Anak Tk Di Kelurahan Baluwarti, Kecamatan Pasar Kliwon, Surakarta Tahun 2015/2016 - KUSWARDANI, RESITA SAPRELIA, Drs. Ilham Sunaryo, M.Pd AUD (2016)
The family is the child's closest environment, especially the parents. Parents have an important role in the formation of the child's personality. This study aims to determine the relationship between democratic parenting style to discipline Baluwarti kindergarten children in Pasar Kliwon, Surakarta, Academic Year 2015/2016. This study used a descriptive correlational design. The population in this study was 121 children and the sample was of 92 children it was using proportional random sampling. Data collection technique used questionnaires for parents and teachers. Data analysis of this study used product moment correlation analysis. Based on the analysis of Pearson product moment correlation r it was obtained 0.503 with a significance of 0.000 <0.01 (p = 0.000; p <0.01) in. Thus it could be concluded that there was a positive correlation between democratic parenting style to discipline kindergarten children in Sub Baluwarti Pasar Kliwon Surakarta Academic Year 2015/2016.